POTENSI NANOKOLAGEN LIMBAH SISIK IKAN SEBAGAI COSMECEUTICAL - Hanny Setyowati; Wahyuning Setyani (Jurnal Farmasi Sains dan Komunitas (Journal of Pharmaceutical Sciences and Community), 2015)
Abstract: Collagen is the most abundant protein of white connective tissue, comprising approximately 30% of total animal protein. This is a fibrous protein which give strength and flexibility in the tissue and bone, also playing an important role for skin and tendon. The utilization of collagen from fish scales waste become an alternative for medication (pharmaceutical), and daily care as cosmetic, which known by cosmeceutical. Nanotechnology application can be completing of cosmeceutical, not only for cure, but also for daily treatment using an wasted materials changed into beneficial product to be developed. Keywords : collagen, fish scales waste, cosmeceutical